Efficacy and safety of acupuncture and moxibustion for herpes zoster: A protocol for systematic review and network meta analysis - Zhang, Na (Medicine (Baltimore), 2020)
INTRODUCTION: Herpes zoster (HZ) is currently treated primarily with antiviral drugs, yet this treatment has been debated. Acupuncture is becoming a more important treatment in this protocol. For example, pain intensity is lower among HZ patients who receive acupuncture plus moxibustion than among those who receive pharmacotherapy. There are many types of acupuncture interventions, including electroacupuncture, moxibustion, bloodletting. In this study, a network meta-analysis (NMA) is used to rank various interventions of acupuncture. METHODS AND ANALYSIS: Electronic searches of abstracts and titles will be performed in MEDLINE, EMBASE, CENTRAL, CBM, CNKI, CQVIP, and Wanfang Data databases, from inception to December 31, 2019. Published and unpublished controlled trials with different acupuncture interventions will be selected, trials of antiviral drugs as the control group. All patients of HZ will be included, except for those diagnosed with PHN, immunocompromised patients, or those with complications. The effective therapy rate and the incidence of PHN are primary outcomes. The NMA will be analyzed with Stata 13.0 and GeMTC 0.14.3. DISCUSSION: The NMA will be established to compare various interventions of acupuncture for the therapy of HZ, that could resolve the limitations of previous methodologies with this protocol. It will be possible to determine the best acupuncture intervention for more primary outcomes of therapy, including subgroup analysis of patients with aged ≥50 years and those of aged <50 years. ETHICS AND DISSEMINATION: The NMA does not require ethical approval. The data analyzed is not personal. It is only systematically used to evaluate the effectiveness of acupuncture treatments. The results will be disseminated through international conference reports and peer-reviewed manuscripts. STRENGTH AND LIMITATIONS OF THIS STUDY: A comprehensive methodology is established to rank various interventions of acupuncture by which best evidence-based intervention may be recommended for those population groups of aged ≥50 years and aged <50 years. PROSPERO REGISTRATION NUMBER: CRD42019118369.